The Problem of Inadmissibility in Secondary Schools - Sherimbetova, Z. Sh.; Tlewmuratova, A. (European Journal of Life Safety and Stability (2660-9630), 2023)
The mastering problem is one of the main problems in secondary schools. It requires thorough approaches to study and eliminate these.